Personal Epistemology and Self-Efficacy in the Special Education Teacher - Johnson, Bradley W. (Journal of the American Academy of Special Education Professionals, 2011)
This report summarizes the personal epistemology and self-efficacy concepts and how they affect special education teachers. This report is based on the social cognitive theory, perceived and collective efficacy, and how the conceptual thoughts of a special education teacher affect their instructional focus in the classroom. Self-efficacy beliefs are identified from four principals of information: enactive mastery experiences, vicarious experiences, verbal persuasion, and physiological and affective states. These concepts are important for special education teachers and the administration alike to help the instructional and learning environment.